Enhancing dyscalculia identification through an innovative 3d game framework - Salam, Sazilah; Pudjoatmodjo, Bambang; Che Pee, Ahmad Naim; Rudavan, Rikman Aherliwan (Universiti Teknologi MARA, Kedah, 2023)
This study focuses on academic learning difficulties, particularly dyscalculia—a learning disorder affecting individuals with average to high intelligence. The subtle nature of dyscalculia complicates its identification, often resulting in students being inaccurately perceived as disinterested or lacking motivation, which in turn erodes their self-confidence. To tackle this challenge, our research introduces an inventive strategy that utilizes a game framework for dyscalculia identification, built upon the foundational Petri-Net storytelling structure. This approach seamlessly integrates within 3D gaming environments, discreetly assessing mathematical prowess without inducing assessment-related stress. Referred to as the "3D-DIG (3D Dyscalculia Identification Game) Framework," this serious gaming architecture incorporates a dedicated monitoring layer. This layer captures and assesses students' mathematical problem-solving methods as they engage with in-game challenges. Our study yields three key outcomes: i) Development of a proactive 3D Game framework designed to identify potential dyscalculia in students. ii) Creation of an all-encompassing student answer database, documenting misconceptions, and specific learning obstacles. iii) Compilation of video-based assessment records, offering educators insights into students' interactions during in-game challenges. Together, these extensive datasets empower educators with essential tools for accurately pinpointing dyscalculia and providing tailored assistance to affected students. Our innovative approach not only refines the identification process but also contributes to nurturing a more inclusive and supportive learning environment.